2006
DOI: 10.1063/1.2222337
|View full text |Cite
|
Sign up to set email alerts
|

Using infrared laser to enhance field emission of carbon nanotube

Abstract: Infrared laser has been used to irradiate carbon nanotube (CNT) powders and the performance of CNT emitter was enhanced. The CNTs were prepared by conventional electric arc discharge method and laser irradiation was processed by Nd:YAG infrared laser with a wavelength of 1064nm. It was found that the turn-on electric field was significantly decreased for laser treated sample. As compared to the sample of no laser treatment, the emission current density was enhanced by a magnitude of 16.56 for 225J∕cm2 treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, a further increase in laser power density at and above 6 MW/ cm 2 decreased the field-emission current density due to the thermal effect by the energetic laser annealing. 14 Figure 3͑a͒ shows the Raman spectra of CNT cathodes treated with various plasma and laser conditions. The locations of all the D-and G-line peaks are almost not changed, showing the different peak intensities of each peak.…”
Section: Methodsmentioning
confidence: 99%
“…However, a further increase in laser power density at and above 6 MW/ cm 2 decreased the field-emission current density due to the thermal effect by the energetic laser annealing. 14 Figure 3͑a͒ shows the Raman spectra of CNT cathodes treated with various plasma and laser conditions. The locations of all the D-and G-line peaks are almost not changed, showing the different peak intensities of each peak.…”
Section: Methodsmentioning
confidence: 99%
“…7 Field emission devices based on CNTs have been realized using a variety of methods ranging from the chemical vapor deposition (CVD) process, assembling in more complex systems and using screen printed techniques. [16][17][18][19][20][21][22][23][24][25] Several studies have demonstrated an enhancement of electron field emission after laser treatments performed both on screen-printed CNTs and those created using CVD techniques. To achieve high current densities and stability, postsynthesis treatment can be adopted, including thermal, chemical, and laser treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the FE properties of CNTs [6,7] and other material such as ZnO nanowires [8] would be greatly enhanced after laser treatment. With similar structure, graphene may also have the opportunity to improve the FE properties after laser treatment.…”
Section: Introductionmentioning
confidence: 99%